Pengaruh Komunikasi Dan Beban Kerja Terhadap Kinerja Karyawan Pada CV Sari Rasa Nusantara Pal Merah Jakarta Barat - Ikhwani, Muhammad Rifki; Akbar, Irfan Rizka (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
in this study aims to determine the influence of Communication and Workload on the performance of Employees of "CV Sari Rasa Nusantara Pal Merah West Jakarta" partially and simultaneously. The method used in this study is a quantitative method. The population in this study was 62 respondents. The sampling technique used saturated sampling and obtained a sample of 57 respondents. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients, and hypothesis tests. The results of this study are that the Communication variable partially has a positive and significant effect on employee performance with a calculated t value (9,450> 2.004) and a sig value of 0.000 <0.05. This indicates that H0 is rejected and H1 is accepted. The Workload variable partially has a positive and significant effect on employee performance with a calculated t value (6,246> 2.004) a sig value of 0.000 <0.05. This indicates that H0 is rejected and H2 is accepted. Based on the F- hypothesis test (Simultaneous), the calculated F value (49.209 > 3.168) and a significance value of 0.000 < 0.05 are shown. Therefore, it can be concluded that H0 is rejected and H3 is accepted. This means that communication and workload simultaneously have a positive and significant effect on employee performance at CV Sari Rasa Nusantara Pal Merah, West Jakarta. The R-square value is 0.646, or 64.6%, with the remaining 35.6% influenced by other variables not examined in this study.